The impact of dual antiplatelet therapy on bleeding and thrombotic risks in diabetic patients following coronary stent implantation: a prospective study - Fan, Rui; Ma, Yulong (Psycho-oncologie, 2025)
Background: Diabetes mellitus is a significant comorbidity in patients undergoing percutaneous coronary intervention (PCI) with stent implantation, and it is associated with increased risks of bleeding and thrombosis. The optimal duration and intensity of dual antiplatelet therapy (DAPT) in diabetic patients remain a subject of debate due to the delicate balance between thrombotic and bleeding risks. Objective: This prospective study aims to evaluate the impact of DAPT on the risks of bleeding and thrombosis in diabetic patients following coronary stent implantation, and to determine the optimal duration of DAPT in this high-risk cohort. Methods: In this single-center prospective cohort study, 500 diabetic patients receiving drug-eluting stents (DES) were prescribed DAPT (aspirin + P2Y12 inhibitor). Participants were stratified into short-term (<6 months) and extended (≥6 months) DAPT groups based on actual treatment duration. Primary outcomes included major adverse cardiovascular events (MACE: cardiac death, myocardial infarction, target vessel revascularization) and BARC type 2/3/5 bleeding events. Outcomes were adjudicated by an independent blinded committee. 结果：在 12 个月内，与短期治疗相比，延长 DAPT 显著降低了 MACE 发生率 （7.8% vs. 10.5%，HR=0.72,95% CI：0.53-0.98，P = 0.03）。 这一获益是由较低的靶血管血运重建率驱动的 （3.1% vs. 5.1%，P=0.03）。虽然总体出血率没有显著差异 （8.1% vs. 6.2%，P=0.19），但亚组分析显示，既往出血史患者的复发性出血显著增加 （HR=2.10，P=0.01）。 结论：延长 DAPT 可减少糖尿病患者支架植入术后的缺血事件，而不会显着增加总体出血风险。然而，由于出血复发率增加，在有既往出血史的患者中使用需要谨慎。这些发现强调了平衡血栓形成保护和出血易感性的个体化 DAPT 策略的必要性。